IN COMMEMORATION OF THE 100TH ANNIVERSARY OF CONVOCATION OF THE FIRST PAEDIATRICIANS CONGRESS - G. L. Mikirtichan (Вопросы современной педиатрии, 2012)
The article is dedicated to the 100th anniversary of the first Paediatricians Congress in Russian and Soviet history. The author recounts the premises to the Congress convocation in the era of paediatrics formation as a separate field of medical science, explains the role of I. V. Troitski as an initiator of International and All-Russian paediatricians congresses convocation. The scientific program and contents of the main reports of the Congress are discussed in the article.